CHEMICAL AND MORPHOLOGICAL CHANGES IN ARCHAEOLOGICAL SEEDS AND FRUITS DURING PRESERVATION BY DESICCATION - van Bergen P.F.; Bland H.A.; Horton M.C.; Evershed R.P. (My University, 1997)
Soluble and insoluble constituents of modern and ancient (ca. 600 AD) desiccated barley kernels and radish seeds have been studied using high-temperature gas chromatography-mass spectrometry, scanning electron microscopy, and Curie-point pyrolysis-gas chromatography-mass spectrometry. Although some changes in colour are seen, the morphology and anatomy of the desiccated specimens are largely unchanged compared with their extant counterparts. The main chemical alterations arising through long-term desiccation are chemically rather than microbially mediated. Comparison between the lipid data from the modern and ancient barley and radish reveals that extensive ester hydrolysis has occurred over time, while oxidation has been retarded. The insoluble material of the modern barley kernel walls, which is composed of a lignin-cellulose complex characteristic of monocotyledons, undergoes upon desiccation chemical alterations resulting in a significant decrease in the abundance of polysaccharides and cinnamic acids moieties. In marked contrast, the insoluble constituents of the modern radish seed coat yields primarily amino acid moieties upon pyrolysis, most likely deriving from proteins. The seed coat also contains a polyphenolic macromolecule and a small contribution from a dicotyledon lignin-cellulose complex. This is the first time such a distinct chemical composition has been reported for modern sclerotic plant tissues. The chemical composition of the tissues of the ancient radish specimens appears little altered compared with their modern counterparts; the only obvious difference is the decrease in abundance of 2,6-dimethoxyphenol moieties in the lignin-cellulose pyrolysis products. Comparison of the microscopic and chemical data with that of walls of propagules, i.e., fruits and seeds, deposited in aquatic environments reveals no differences between the material deposited under desiccating and aquatic conditions.